2018
DOI: 10.1371/journal.pbio.2005354
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of systemic lupus erythematosus are diagnosed in leptin transgenic pigs

Abstract: Leptin is a well-known adipokine that plays a critical role in immune responses. To further explore the immunological roles of leptin, we developed a transgenic leptin pig controlled by the pig leptin (pleptin) promoter to overexpress leptin. Symptoms typically associated with systemic lupus erythematosus (SLE) were evident in this transgenic pig strain, including anemia, leukopenia, and thrombocytopenia as well as kidney and liver impairment. Histologically, there were increased immunoglobulin G (IgG) levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Yousefian et al also revealed that leptin polymorphisms were related to the risk of MS and its clinical symptoms [ 43 ]. Most recently, Chen et al established a transgenic leptin pig overexpressing leptin and observed manifestations of SLE in this transgenic pig strain [ 44 ]. But a previous study of our group has not discovered the association between leptin polymorphisms with SLE in a Chinese population [ 45 ], which is consistent with previous studies [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yousefian et al also revealed that leptin polymorphisms were related to the risk of MS and its clinical symptoms [ 43 ]. Most recently, Chen et al established a transgenic leptin pig overexpressing leptin and observed manifestations of SLE in this transgenic pig strain [ 44 ]. But a previous study of our group has not discovered the association between leptin polymorphisms with SLE in a Chinese population [ 45 ], which is consistent with previous studies [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the function of the leptin gene in autoimmune diseases has received much attention in recent years [ 42 46 ]. It have been revealed that leptin plays a crucial role in the susceptibility to multiple sclerosis (MS) [ 42 , 43 ] and systemic lupus erythematosus (SLE) [ 44 ]. It also has been reported that leptin -deficient mice had decreased levels of TNF- α and IL-1 β , a less severe arthritis induced by antigen and defective cell-mediated immunity [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The WT and leptin transgenic PFCs were isolated and established from ear tissues of WT and leptin transgenic pigs (Chen et al 2018). The WT and leptin transgenic PFCs were cultured in basic (1×) Dulbecco’s modified Eagle’s medium (DMEM) (Gibco, NY, USA) supplemented with 10% fetal bovine serum (Ausbian, VS500 T) and 100 IU/ml penicillin.…”
Section: Methodsmentioning
confidence: 99%
“…Transgenic expression of leptin in pigs results in a lupus-like disease characterized by increased anti-dsDNA antibodies, renal immune complex deposition, nephritis, and decreased frequency of Treg cells. 97 Leptin levels inversely correlate with the frequency of Treg cells in SLE patients. 83 Leptin deficiency in MRL/lpr lupus-prone mice was protective for disease development, and it increased the frequency of Treg cells.…”
Section: Lupus and Sys Temi C Me Tabolis Mmentioning
confidence: 98%
“…Leptin signaling is necessary for murine Th17 effector functions, and it skews human and mouse T cells toward a Th1 phenotype in vitro, which is relevant to SLE patients who present an increased frequency of Th1 cells and IFNγ production. Transgenic expression of leptin in pigs results in a lupus‐like disease characterized by increased anti‐dsDNA antibodies, renal immune complex deposition, nephritis, and decreased frequency of Treg cells . Leptin levels inversely correlate with the frequency of Treg cells in SLE patients .…”
Section: Lupus and Systemic Metabolismmentioning
confidence: 99%